Exploring audience perception: a case study of Malaysian University students' perspectives before and after viewing portrayals of Autism in drama series - Chua, Benny Yaw Ann (2024)
Autism Spectrum Disorder (ASD) has been a longstanding social issue in Malaysia ever since the country was formed. However, Malaysians do not pay adequate attention to the autism community due to low acceptance and a feudal society. This has caused individuals with autism to be left out by society, as most Malaysians fear to understand and interact with the autism community. Therefore, this study is aimed at analysing perceptions towards the ASD community before and after watching ASD movies and drama series among Malaysian university students. A purposive sampling involving 20 respondents was used for the data collection process. The targeted respondents were Malaysian university students aged 18 to 25 years old, with students aged 21 to 23 being the most represented (n=16). The respondents will complete the first part of the survey and then proceed to the second part after consuming an ASD drama series. Drawing upon Uncertainty Reduction Theory (URT), the findings revealed that the perception of the respondents has changed after the screening session of the ASD drama series. These findings suggest the potential for increased acceptance and empathy towards the ASD community among Malaysian university students. Ultimately, it is hoped that this study will contribute to increasing the enrolment rate of individuals with ASD in local universities and changing perceptions towards the ASD community.